Pharmaceutical-Induced Dyskinesia: A Case Study of Thoracotomy Treated with Amantadine - Mojtaba Mojtahedzadeh; Atabak Najafi; Farahnaz Hosseinzadeh; Fatemeh Saghafi (Case Reports in Clinical Practice)
Dyskinesia, marked by involuntary and irregular movements, can result from various pharmaceutical agents. The case presented features a patient undergoing thoracotomy, experiencing dyskinesia, likely attributed to antipsychotics, antiemetics, and antibiotics, and subsequently treated with amantadine.